Impact of Financial Globalization on Environmental Degradation in the E7 Countries: Application of the Hybrid Nonparametric Quantile Causality Approach - Adebayo, Tomiwa Sunday (Problemy Ekorozwoju, 2022)
Despite their economic success, the E7 countries have not been able to provide environmental protection. These countries, on the other hand, will not be able to maintain their economic progress if they do not also protect their natural resources. In this regard, the goal of this research is to examine the impact of financial globalization on CO2 emissions in the E7 countries. Utilizing a quarterly dataset between 1990Q1 and 2018Q4, we applied the novel quantile-on-quantile regression (QQR) and nonparametric causality in quantiles approaches to assess these interconnections. Furthermore, the quantile cointegration outcomes revealed cointegration between financial globalization and CO2 in each of the E7 nations. Furthermore, the QQR outcomes disclosed that in the majority of the quantiles, the effect of financial globalization on CO2 is positive for Brazil, China, India and Turkey, thus validating the pollution-haven-hypothesis. Moreover, for Indonesia, Russia and Mexico, in the majority of the quantiles, the effect of financial globalization on CO2 is negative, therefore validating the pollution-halo hypothesis. Moreover, the novel causality in quantiles approach disclosed that financial globalization can predict CO2 emissions for the E7 nations. Therefore, any policy channeled towards financial globalization will have a significant influence on CO2 emissions in the E7 economies. In light of these significant observations, the research suggests that Mexico, Russia, and Indonesia should be more financially interconnected, whereas China, India, Turkey, and Brazil should reevaluate their financial globalization policies.